Active controllable and flexible winding needle an option to reduce the complexity of needle winding machines and the stress on enameled wire - Schneider, Michael; Bickel, Benjamin; Risch, Florian; Franke, Jörg (2014 4th International Electric Drives Production Conference, EDPC 2014 - Proceedings, 2014)
State of the art needle winding technologies have one thing in common-a stiff, straight or bent winding needle. During the manufacturing process of electrical machines, the used enameled wires are exposed to deformations which decrease the insulation resistance against partial discharge and disruptive discharge. A reduced insulation resistance shortens the product lifecycle. The active controllable and flexible winding needle is able to adapt its form to the mechanical behavior of wire during any deformation and thus to wind wires more gently. In the production of electrical machines the copper filling factor in the slot is often considered key. To provide the needed space for the tools to move through the stator while distributing the windings, the winding tools have to be rather small or the inner diameter of the stator has a minimum whereat the feasibility for needle winding is still present. With the actively controllable and flexible winding needle no more extra axis and other constructions are necessary to fulfill the requirements of a small tool at maximum flexibility.
CRIS-Team Scopus Importer:2023-03-07
Keywords: distributed winding; winding guide nozzle; winding needle; winding technology